A REVIEW ON LEVOFLOXACIN INSITU GEL - ANSHUL, SAXENA; RENU, SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Eye drops that are conventional ophthalmic delivery systems often result in poor bioavailability and therapeutic response, because high tear fluid turns over and dynamics cause rapid precorneal `elimination of the drug. A high frequency of eye drop instillation is associated with patient non-compliance. Inclusion of excess drug in the formulation is an attempt to overcome bioavailability problem is potentially dangerous if the drug solution drained from the eye is systemically absorbed from the Nasolachrymal duct. Various ophthalmic vehicles such as inserts, ointments, Suspensions and aqueous gels have been developed in order to lengthen the residence time of instilled dose and enhance the ophthalmicbioavailability.These ocular drug delivery system show ever have not been used extensively because of some drawbacks such as blurred vision from ointments or low patient compliance from inserts.